Taqwim Fa'iliyyah Dalil al-Musafir li al-Tawasul bi al-Lughah al-Arabiyyah 'Abra al-Hawatif al-Zakiyyah li al-Mutawwifin al-Maliziyyin - Zubir, Muhamad Azhar; Sahrir, Muhammad Sabri; Ismail, Taufik (Penerbit UPSI, Perak Darul Ridzuan., 2021)
A book chapter in published book by UPSI.